2020
DOI: 10.1177/0265407520967438
|View full text |Cite
|
Sign up to set email alerts
|

Political difference and polarization in the family: The role of (non)accommodating communication for navigating identity differences

Abstract: This study joins the relatively modest literature examining the effects of political disagreement in the family. We consider the effects of communication accommodation on shared family identity in the context political disagreement. To do this, we utilize survey responses from a quota-stratified sample of participants in an online panel ( N = 833) taken immediately after the contentious 2016 presidential election. We find that more disagreement and more affective polarization are associated with less communica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 52 publications
(83 reference statements)
1
35
0
Order By: Relevance
“…If an analogy to country-level political decision-making is used, our findings suggest that people's willingness to accept political decisions is influenced by whether they feel respected by their fellow citizens from the opposite opinion group. This is in line with recent research in the area of political polarization showing that affective polarization in society is reduced by respectful disagreement rather than by a policy compromise (Huddy & Yair, 2020) and that family communication respectful of divergent values is crucial in handling political differences within a family (Warner et al, 2020). Future research could elaborate on the sources of perceived respect.…”
Section: Discussionsupporting
confidence: 83%
“…If an analogy to country-level political decision-making is used, our findings suggest that people's willingness to accept political decisions is influenced by whether they feel respected by their fellow citizens from the opposite opinion group. This is in line with recent research in the area of political polarization showing that affective polarization in society is reduced by respectful disagreement rather than by a policy compromise (Huddy & Yair, 2020) and that family communication respectful of divergent values is crucial in handling political differences within a family (Warner et al, 2020). Future research could elaborate on the sources of perceived respect.…”
Section: Discussionsupporting
confidence: 83%
“…Individuals should be mindful of the relational impact of different preferences for the quantity or quality of media consumption. Political differences tend to generate barriers to relational solidarity, yet the negative effect of political differences on relationships can be mitigated through accommodative communication ( Warner et al, in press ). Accommodative communication involves topic selection, communicating respect about differing opinions, limiting self-disclosure on contentious topics, and expressing tolerance for others’ beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Furman and Buhrmester (1992) found friendships and romantic relationships were more egalitarian than parent-child relationships, and research has shown when someone has less power they are more likely to experience psychological aggression from their relational partner (Dunbar and Johnson, 2015). Additionally, Warner et al (2020) found when people disagree with their family members, they are less likely to engage in respectful communication when discussing those differences. Therefore, people might expect worse relationship outcomes when declining an event from a family member than a friend or romantic partner.…”
Section: Relational Implications Of Refusalsmentioning
confidence: 97%